Life cycle impact assessment of recycled aggregate concrete, geopolymer concrete, and recycled aggregate-based geopolymer concrete - Imtiaz, L. (MDPI, 2021)
This study presents a life cycle impact assessment of OPC concrete, recycled aggregate concrete, geopolymer concrete, and recycled aggregate-based geopolymer concrete by using the mid-point approach of the CML 2001 impact-assessment method. The life cycle impact assessment was carried out using OpenLCA software with nine different impact categories, such as global warming potential, acidification potential, eutrophication potential, ozone depletion potential, photochemical oxidant formation, human toxicity, marine aquatic ecotoxicity, and freshwater and terrestrial aquatic ecotoxicity potential. Subsequently, a contribution analysis was conducted for all nine impact categories. The analysis showed that using geopolymer concrete in place of OPC concrete can reduce global warming potential by up to 53.7. Further, the use of geopolymer concrete represents the reduction of acidification potential and photochemical oxidant formation in the impact categories, along with climate change. However, the potential impacts of marine aquatic ecotoxicity, freshwater aquatic ecotoxicity, human toxicity, eutrophication potential, ozone depletion potential, and terrestrial aquatic ecotoxicity potential were increased using geopolymer concrete. The increase in these impacts was due to the presence of alkaline activators such as sodium hydroxide and sodium silicate. The use of recycled aggregates in both OPC concrete and geopolymer concrete reduces all the environmental impacts. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.